The Relationship Between Service Quality and Patient Satisfaction at the Neurology Polyclinic of Mohammad Natsir Hospital - Fitri Sari Susanty; Nur Afrainin Shah; Wihardi Triman (Journal of Social Research, 2023)
Quality health services are the needs and desires of every patient. Patient satisfaction is related to the quality of service they receive. This study analyzed the relationship between service quality and patient satisfaction at the neurology polyclinic of the Mohammad Natsir Solok Regional General Hospital (RSUD). Service quality according to Zeithaml et al has five dimensions, namely: Reliability, Assurance, Tangibles (physical evidence), Empathy (empathy), and Responsiveness knew as SERVQUAL. The purpose of this study is to determine the relationship between each dimension of service quality and patient satisfaction and find out the dimensions that most affect patient satisfaction. This research is a quantitative study with a cross-sectional study approach with a total sample of 100 people. Data collection using questionnaires. Data analysis in the form of univariate analysis, bivariate analysis using chi-square, and multivariate analysis using multiple logistic regression. The univariate analysis found that general patient satisfaction with the quality of service was 86% satisfied with the service. Bivariate analysis showed a significant relationship between the dimensions of reliability (p = 0.001), assurance (p = 0.001), tangibles (p = 0.009), empathy (p = 0.001) and responsiveness (p = 0.001) with patient satisfaction. The multivariate analysis found that the dimension that most affected patient satisfaction at the neurology polyclinic of Mohammad Natsir Hospital was the responsiveness dimension (OR = 73,635).